Wage differentials across sectors in Europe: an east-west comparison - Iga Magda; François Rycx; Ilan Tojerow; Daphné Valsamis (Institute for the Study of Labor (IZA), 2008)
This study compares the structure and determinants of inter-industry wage differentials in Eastern and Western European countries (namely Belgium, Italy, the Netherlands, Norway, Portugal and Spain compared with Latvia, Lithuania, the Czech Republic, Poland and Slovakia). To do so, we use a unique harmonised, linked employer-employee data set, the 2002 European Structure of Earnings Survey. Findings show substantial differences in earnings across sectors in all countries, even when controlling for a wide range of employee, job and employer characteristics. The hierarchy of sectors in terms of wages appears to be quite similar in Eastern and Western European countries. Among high-wage sectors, we find the energy (coke, petroleum, gas, electricity and nuclear power), chemical, financial and computer industries. In contrast, it is in the traditional sectors (wood and cork industry, textile, clothing and leather industry, hotels and restaurants, and retailing) that wages are lowest. Further results suggest that the dispersion of inter-industry wage differentials fluctuates considerably across countries. It is relatively small in Norway and Belgium, large in the Netherlands, Italy, Spain, Poland and the Czech Republic, and very large in Portugal, Latvia, Lithuania and Slovakia. Our findings support the hypothesis of a negative relationship between the dispersion of inter-industry wage differentials and a country's degree of corporatism.
urn:nbn:de:101:1-20081127595
Keywords: J31; 330; Inter-industry wage differentials; collective bargaining; Europe; matched employer-employee data; Sektorale Lohnstruktur; Tarifpolitik; Vergleich; Westeuropa; Osteuropa; Belgien; Italien; Niederlande; Norwegen; Portugal; Spanien; Lettland; Litauen; Tschechische Republik; Polen; Slowakei